Bone marrow versus mobilized peripheral blood stem cells in haploidentical transplants using posttransplantation cyclophosphamide. Issue 7 (23rd January 2018) - Ruggeri, Annalisa; Labopin, Myriam; Bacigalupo, Andrea; Gülbas, Zafer; Koc, Yener; Blaise, Didier; Bruno, Benedetto; Irrera, Giuseppe; Tischer, Johanna; Diez‐Martin, Jose Luiz; Castagna, Luca; Ciceri, Fabio; et al.
Abstract : BACKGROUND: Incidence of graft‐versus‐host disease (GVHD) in haploidentical bone marrow (BM) transplants using posttransplantion cyclophosphamide (PT‐Cy) is low, whereas GVHD using mobilized peripheral blood stem cells (PBSC) ranges between 30% and 40%. METHODS: To evaluate the effect of stem cell source in haploidentical transplantation with PT‐Cy, we analyzed 451 patients transplanted for acute myeloid leukemia or acute lymphoblastic leukemia reported to the European Society for Blood and Marrow Transplantation. RESULTS: BM was used in 260 patients, and PBSC were used in 191 patients. The median follow‐up was 21 months. Engraftment was lower in BM (92% vs 95%, P < 0.001). BM was associated with a lower incidence of stage II‐IV and stage III‐IV acute GVHD (21% vs 38%, P ≤ .01; and 4% vs 14%, P < .01, respectively). No difference in chronic GVHD, relapse, or nonrelapse mortality were found for PBSC or BM. The 2‐year overall survival (OS) was 55% versus 56% ( P = .57) and leukemia‐free survival (LFS) was 49% versus 54% ( P = .74) for BM and PBSC, respectively. On multivariate analysis, PBSC were associated with an increased risk of stage II‐IV (hazard ratio [HR], 2.1; P < .001) and stage III‐IV acute GVHD (HR, 3.8; P < .001). For LFS and OS, reduced intensity conditioning was the only factor associated with treatment failure (LFS: HR, 1.40; P = .04) and relapse (HR, 1.62; P = .02). CONCLUSION: In patients with acute leukemia in first or second remission receiving haploidentical transplantation with PT‐Cy, the use of PBSC increases the risk of acute GVHD, whereas survival outcomes are comparable. Cancer 2018;124:1428‐37 . © 2018 American Cancer Society . Abstract : For patients with acute leukemia in complete remission, the use of peripheral blood stem cells (PBSC) significantly increases the risk of acute graft‐versus‐host disease (GVHD) compared with bone marrow (BM) in haploidentical transplantation with posttransplantion cyclophosphamide (PT‐Cy). Chronic GVHD and survival outcomes are comparable in PBSC versus BM recipients in haploidentical transplantation with PT‐Cy.